Gibrat’s law and liquidity constraints: evidence from Malaysia industrial sector companies - Harkati, Rafik; Mohamad, Azhar (IIUM Press, 2016)
Gibrat’s Law, or the Law of Proportionate Effect (LPE), presupposes that the growth rate of a given company is independent of its initial size. While older studies have a tendency to confirm the LPE, recent studies generally reject it. Only very few empirical studies have examined the validity of Gibrat’s Law in developing countries, with most studies focused on developed countries. In this study, we investigated the validity of the LPE in Malaysia. We also investigated whether liquidity constraints have any influence on firm growth and firm growth-size dynamics. By employing the Generalized Method of Moments (GMM) system to estimate a panel data model of the firm growth of 210 firms that were part of the Malaysian industrial sector from 2005 to 2014, we found that Gibrat’s Law was invalid and liquidity constraints had no role in explaining both the firms’ growth and growth-size dynamics, whereas age was found to positively affect the firms’ growth.